Potensi Pengembangan Mikro Hidro Sungai Pasak Suling Kabupaten Gunung Mas Kalimantan Tengah: Micro Hydro Development Potential Of Pasak Suling River Gunung Mas District, Central Kalimantan - Anggen, Apu R. (Media Ilmiah Teknik Sipil, 2021)
Community in Desa Karason Raya District Tewah have no access to the State Electricity Network (PLN), when electricity is needed for development in this village. Karason Raya Village has potential of water resources that can be used as a generator of Micro Hydro Power Plant (MHPP) but these resources are not optimally explored. This study aims to determine the socio-economic conditions, geological conditions, hydrology. The amount of power that can be provided by the Micro Hydro Power Plant (MHPP) and the strategies when the Micro Hydro Power Plant (MHPP) wll be developed by SWOT Analysis. Research is done in Desa Karason Raya District Tewah. Methodology used was secondry data analysis, interviews, and field observations to obtain the necessary data. Results showed that the type of Malihan Pinoh rock (PzRp) composed of fillit , kis, quartize and genealogy. The slope of ground conditions along Sungai Pasak suling tributary quite steep on both the river are rocky hills that are not symmetrical. Calhmet wide area 7.50 Km², 1.30 m³/sec measureable water discharge, 13 metres high water fall and potential generated power of 168.339,60 watts